Sensitivity and effectiveness analysis of incentives for concentrated solar power projects in Chile. (December 2018) - Simsek, Yeliz; Mata-Torres, Carlos; Guzmán, Amador M.; Cardemil, Jose M.; Escobar, Rodrigo
Abstract: Northern Chile has excellent conditions to develop concentrated solar power projects. Although solar irradiation makes a significant contribution to production in the region, solar thermal projects need some support mechanisms. This study focuses on the best combinations of solar incentives and financial parameters to have lowest government cost and maximum levelized cost of electricity reduction. Key findings of this paper showed that debt fraction and discount rate illustrated meaningful sensitivities on both LCOE and government cost. ITC, PTC, and DM as tax credit and PBI as cash incentives had the best effectiveness, and reduced LCOE better than IBI and STR. The effectiveness of ITC, PTC, PBI, and DM was independent of financial parameters even though STR and IBI showed dependency. Although cash incentives had no limits to reduce LCOE, tax credit incentives reached maximum values, which meant that their impacts were limited. As cash incentives, PBI showed better results when it was compared to IBI. Maximum values of ITC maintained the same for different installed costs, while it changed for PTC. Finally, it was obtained that tax credit incentives were more meaningful at higher PPA price although PBI made more sense in lower PPA prices. Highlights: Debt fraction and discount rate illustrated meaningful sensitivities on both LCOE and government cost. ITC, PTC, DM and PBI had the best effectiveness, and reduced LCOE better than IBI and STR. The effectiveness of these incentives was independent of financial parameters even though STR and IBI showed dependency. Although cash incentives had no limits to reduce LCOE, tax credit incentives reached maximum values, which meant that their impacts were limited. As cash incentives, PBI showed better results when it was compared to IBI. Maximum values of ITC maintained the same for different installed costs, while it changed for PTC. Finally, it was obtained that tax credit incentives were more meaningful at higher PPA although PBI made more sense in lower PPA.